Acupuncture therapy on myofascial pain syndrome: a systematic review and meta-analysis - Xiong, Jingwen; Zhou, Xuancheng; Luo, Xiufang; Gong, Xiangjin; Jiang, Lai; Luo, Qiang; Zhang, Shengke; Jiang, Chenglu; Pu, Tong; Liu, Jie; Zhang, Jun; Li, Bo; et al. (Frontiers in Neurology, 2024)
Purpose Traditional Chinese medicine (TCM) therapies, especially acupuncture, have received increasing attention in the field of pain management. This meta-analysis evaluated the effectiveness of acupuncture in the treatment of myofascial pain syndrome. Methods A comprehensive search was conducted across a number of databases, including PubMed, Cochrane Library, WOS, CNKI, WANFANG, Sinomed, and VIP. Furthermore, articles of studies published from the inception of these databases until November 22, 2023, were examined. This systematic review and meta-analysis encompassed all randomized controlled trials (RCTs) on acupuncture for myofascial pain syndromes, without language or date restrictions. Based on the mean difference (MD) of symptom change, we critically assessed the outcomes reported in these trials. The quality of evidence was assessed using the Cochrane Risk of Bias Tool. The study is registered with PROSPERO under registration number CRD42023484933. Results Our analysis included 10 RCTs in which 852 patients were divided into two groups: an acupuncture group (427) and a control group (425). The results of the study showed that acupuncture was significantly more effective than the control group in treating myofascial pain syndromes, which was reflected in a greater decrease in VAS scores (MD = −1.29, 95% [−1.65, −0.94], p < 0.00001). In addition, the improvement in PRI and PPI was more pronounced in the acupuncture group (PRI: MD = −2.04, 95% [−3.76, −0.32], p = 0.02) (PPI: MD = −1.03, 95% [−1.26, −0.79], p < 0.00001) compared to the control group. These results suggest that acupuncture is effective in reducing myofascial pain. It is necessary to further study the optimal acupoints and treatment time to achieve the best therapeutic effect. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023484933.